Overview of Premarital Sexual Behavior at Risk of Pregnancy Termination in Adolescent Girls in Indonesia - Aminatussyadiah, Ayu; Wardani, Suci Fitriana Pramudya (Universitas Muhammadiyah Semarang, 2025)
Globally around 16 million girls in the world aged between 15 to 19 years and about 1 million girls under the age of 15 give birth each year. Complications during pregnancy and childbirth are the second leading cause of death for girls aged 15-19 worldwide. Every year, about 3 million girls aged 15 to 19 years have unsafe abortions. Babies born to mothers who are teenagers have a much higher risk of death than those born to women aged 20 to 24 years. This study aims to determine what factors influence risky teenage sexual behavior. The type of research used is descriptive quantitative. Research subjects adolescents who engage in risky sexual behavior aged 15-24 years. The results showed that there were residential relationships, media exposure and peers with risky sexual behavior. The dominant factor that influences is media exposure.